Orthopedic trauma or surgery does not effect on cognitive_x000D_ or behavioral capability of rats - AKDENİZ, ESRA (My University, 2020)
Aim: The aim of this study is to investigate the probable effects of orthopedic trauma/surgery on anxiety, memory and learningcapability in rats.Material and Methods: Twenty-one Wistar albino rats grouped into three as control, sham operated, and tibia fracture. In controlgroup, any surgery or fracture was done whereas in sham group the tibia of rats was fixed with intramedullar Kischner wire. In tibiafracture group, a closed fracture was occurred with Bonnarens and Einhorn's guillotine device then intramedullar Kischner wiresends to tibia. All rats were evaluated for memory, anxiety, and learning via behavioral tests respectively; water-maze test, elevatedplus arm test and shuttle box test.Results: One month after the fractures were done and the bone healing was seen on X-ray at all rats. According to the behavioraltests results, there was not any statistically difference between groups in terms of anxiety, learning capability, locomotor activity andmemory (p>0.05).Conclusion: Our results showed that, the orthopedic trauma or surgery itself does not affect the anxiety, learning capability, locomotoractivity and memory in rats.